2015
DOI: 10.1080/15532739.2015.1075928
|View full text |Cite
|
Sign up to set email alerts
|

Using Photovoice, Latina Transgender Women Identify Priorities in a New Immigrant-Destination State

Abstract: Little is known about the immigrant Latino/a transgender community in the southeastern United States. This study used photovoice, a methodology aligned with community-based participatory research, to explore needs, assets, and priorities of Latina transgender women in North Carolina. Nine immigrant Latina male-to-female transgender women documented their daily experiences through photography, engaged in empowerment-based photo-discussions, and organized a bilingual community forum to move knowledge to action. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“…Recruiters gave out rubber bracelets that included the study logo and telephone number and showed potential participants examples of incentives, including T-shirts and caps with the logo and a framed certificate of completion with staff and PI signatures. In addition, recruiters emphasized that participating in a study could provide the opportunity to make new friends or meet others with similar experiences to their own, if the study included a group activity (as in the case of data collection through focus groups [25] or photovoice [26] or participation in an intervention [18]).…”
Section: Resultsmentioning
confidence: 99%
“…Recruiters gave out rubber bracelets that included the study logo and telephone number and showed potential participants examples of incentives, including T-shirts and caps with the logo and a framed certificate of completion with staff and PI signatures. In addition, recruiters emphasized that participating in a study could provide the opportunity to make new friends or meet others with similar experiences to their own, if the study included a group activity (as in the case of data collection through focus groups [25] or photovoice [26] or participation in an intervention [18]).…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare service limitations, such as lack of confidentiality, stigma, and a lack of mental health and medical providers qualified to work with transgender persons, exacerbate rural transgender persons’ psychological distress (Willging, Salvador, & Kano, 2006). Although personal and family pride and community belonging may serve as buffers against suicidality for rural individuals (Hirsch & Cukrowicz, 2014), transgender persons consistently experience marginalization, isolation, and deficits in family and social support (Budge, Katz-Wise, et al, 2013; Koken, Bimbi, & Parsons, 2009; Nemoto, Bödeker, & Iwamoto, 2011; Rhodes et al, 2015). Thus, protective factors for rural transgender persons may be limited.…”
mentioning
confidence: 99%
“…Not only does this method provide images of lived experiences, but it also gives an opportunity for participants and others who may be able to support action to collaboratively identify next steps (Hergenrather, Rhodes, Cowan, Bardhoshi, & Pula, 2009). We have successfully used photovoice with Latino men (Rhodes, Hergenrather, Griffith, et al, 2009), persons with HIV (Rhodes, Hergenrather, Wilkin, & Jolly, 2008), Latina transgender women (Rhodes, Alonzo, Mann, Sun, et al, 2015), and the Korean immigrant community (Rhodes, Song, et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…For example, during our photovoice project in partnership with Latina transgender women, we discovered the need for more access to sexual health information and services, a finding that aligns with the existing literature on high rates of HIV among transgender women. However, photovoice participants emphasized that access to transition-related healthcare services, including safe hormone use, was a more urgent priority, particularly given the importance of transition-related services for overall well-being, the risks involved with unsafe hormone use, and barriers to health care such as high rates of being uninsured, limited availability of bilingual and bicultural health services, and the lack of culturally congruent transgender-focused services (Rhodes, Alonzo, Mann, Sun, et al, 2015). Thus, some members of our partnership developed the ChiCAS intervention to focus jointly on sexual health and transition-related health based on these qualitative data and on our enhanced understanding of community needs.…”
Section: Resultsmentioning
confidence: 99%